2013
DOI: 10.3390/en6031456
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Energy CO2 Emissions Using a Quantum Harmony Search Algorithm-Based DMSFE Combination Model

Abstract: Abstract:The accurate forecasting of carbon dioxide (CO 2 ) emissions from fossil fuel energy consumption is a key requirement for making energy policy and environmental strategy. In this paper, a novel quantum harmony search (QHS) algorithm-based discounted mean square forecast error (DMSFE) combination model is proposed. In the DMSFE combination forecasting model, almost all investigations assign the discounting factor (β) arbitrarily since β varies between 0 and 1 and adopt one value for all individual mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…In other studies, various methods are utilized differently, and their applications vary in context. Chang, Sun and Gu [13] presented a novel quantum harmony search (QHS) algorithm-based discounted mean square forecast error (DMSFE) combination model to forecast energy CO 2 emissions. This study's finding was able to certify the validity of the presented approach, while it also revealed that the forecasting precision can be enhanced to a certain degree.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other studies, various methods are utilized differently, and their applications vary in context. Chang, Sun and Gu [13] presented a novel quantum harmony search (QHS) algorithm-based discounted mean square forecast error (DMSFE) combination model to forecast energy CO 2 emissions. This study's finding was able to certify the validity of the presented approach, while it also revealed that the forecasting precision can be enhanced to a certain degree.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The concept of quantum computing is presented by Benioff [49] and Feynman [50] in the 1980s through combing quantum theory and information science. In quantum computing, the qubit is adopted to express the information; and the theory of superposition, entanglement and collapse of states is employed for information computation [39,40,42,51]. Quantum computing greatly improves the computational efficiency and has attracted widespread interest and research.…”
Section: Quantum Harmony Search Algorithm (Qhsa)mentioning
confidence: 99%
“…In classical HSA, the algorithm chooses an upper neighboring value with 50% probability and lower with 50% around new vector. Inspired by Fibonacci theorem, 0.618 is chosen as the border of vector adjusting direction, shown in Equation (12) [51,53].…”
mentioning
confidence: 99%
“…The wide ranging models that have been adopted range from state space and dynamic computable general equilibrium models to the use of quantum harmony search algorithms. Whilst this paper is not interested in presenting an extensive literature coverage, those interested are directed to read some recent articles such as [5][6][7][8][9][10][11][12][13]. Noteworthy is that none of the research (both recent and historical) is able to produce a single forecasting model that outperforms the rest, as each evaluated model appears to have its own advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy is that none of the research (both recent and historical) is able to produce a single forecasting model that outperforms the rest, as each evaluated model appears to have its own advantages and disadvantages. Furthermore, there has been emphasis on providing combination forecasts for CO 2 emissions [13]. In this paper, the SSA technique is introduced as an addition to the already wide ranging list of models for forecasting CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%